Colorado water, January 2020 - Lipscomb, Beth, editor; Colorado Water Center, Colorado State University, publisher (Colorado State University. Libraries, 2020)
Newsletter of the Colorado Water Center. Theme: Research reports.
The newsletter is devoted to highlighting water research and activities at CSU and throughout Colorado.
Keywords: Water resources development -- Colorado; Water use -- Colorado; Water-supply -- Colorado; Water-supply -- Management -- Colorado